Strategi Pendidikan Akhlak dalam Mata Kuliah Ilmu Pendidikan Islam Berbasis Nilai-Nilai Ibadurrahman - Maryono; Ulien Nuha, Zaki (Kartika: Jurnal Studi Keislaman, 2026)
This study explores moral education strategies implemented in the Islamic Education (Ilmu Pendidikan Islam) course at STAI Ali bin Abi Thalib Surabaya by using the Qur’anic concept of ‘Ibadurrahman as the foundation for character formation. The academic concern underlying this research is the need to strengthen moral development among students through learning approaches that are practical, integrative, and grounded in Islamic values. The study aims to identify the strategies applied by lecturers and analyze how these strategies are implemented through learning activities that promote humility, patience, consistency in worship, social compassion, and self-restraint. This research employs a descriptive qualitative method, with data obtained from open-ended questionnaires, documentation, and analysis of course syllabi. The participants in this study consist of 25 students. The findings reveal that moral education becomes effective when it integrates role-modelling, habituation, experiential learning, moral exhortation, and explicit value integration within the syllabus. The implementation of these strategies through tafsir assignments, practical moral projects, and ongoing monitoring successfully increases students’ awareness and efforts to embody several ‘Ibadurrahman qualities. The results also indicate that moral internalization is more optimal when supported by a consistent academic environment that reinforces Qur’anic character. These findings contribute to the development of character-based learning models in Islamic higher education